Healing of normal and osteopenic bone with titanium implant and low-level laser therapy (GaAlAs): a histomorphometric study in rats - Reis de Vasconcellos, Luana Marotta [UNESP]; Moreira Barbara, Mary Anne [UNESP]; Deco, Camila Porto [UNESP]; Junqueira, Juliana Campos [UNESP]; Prado, Renata Falchete do [UNESP]; Anbinder, Ana Lia [UNESP]; Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Alves Cairo, Carlos Alberto; Carvalho, Yasmin Rodarte [UNESP] (Springer, 2014)
The study investigates the influence of low-level laser therapy (LLLT) on bone healing in the femur of osteopenic and normal rats with titanium implants. Ovariectomy and control group were randomly submitted to LLLT, which was applied by gallium-aluminum-arsenium (GaAlAs) laser at the surgical site before and after placing the implant, for seven times. Histomorphometric and statistical analysis were performed. Most irradiated groups showed higher values than the nonirradiated groups. The GaAlAs infrared diode laser may improve the osseointegration process in osteopenic and normal bone, particularly based on its effects in the initial phase of bone formation.
Keywords: Bone; Bone-to-implant contact; Ovariectomy; Laser therapy; Osteopenia